Online College Education: Expanding Opportunities or Reducing Gaps? - Manurung, Lengsi; Thertina, Erlis; Edward, Ruben (Candradimuka: Journal of Education, 2025)
The rise of online learning has had an overall impact on higher education. However, there are concerns that the current gaps will worsen. This article investigates the potential of online teaching to expand higher education and whether its potential downsides will exacerbate existing imbalances.  The purpose of this study is to determine the initial conditions of learning and design an online learning program that focuses on the design of the course system to support the efficiency and effectiveness of learning. Improving the quality of the curriculum and lectures and improving student competence are the expected impacts of this development. This type of research uses quantitative and qualitative methods by surveying questions, questionnaires and using a literature review. The population was taken from 34 students who were randomly selected at a private university in East Jakarta. The results of this study concluded that the results of the 34 respondents surveyed about how effective online learning was for university students in East Jakarta were 76% effective & 24% not yet effective.